2010
DOI: 10.1002/sia.3311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate surface topography on forensic development of latent fingerprints with iron oxide powder suspension

Abstract: Latent fingerprint deposition and effectiveness of detection are strongly affected by the surface on which prints are deposited. Material properties, surface roughness, morphology, chemistry and hydrophobicity can affect the usefulness or efficacy of forensic print development techniques. Established protocols outline appropriate techniques and sequences of processes for broad categories of operational surfaces. This work uses atomic force microscopy and scanning electron microscopy to investigate a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 16 publications
2
48
0
Order By: Relevance
“…These analyses indicate zinc nanoparticle decoration of polycyanoacrylate fibrils, as well as zinc deposition associated with areas of fingermark ridges away from effective CA development. This process may relate to the improved definition of the print seen in other works (2,5,11) through zinc deposition on the nodular structure formed by superficial CA treatment, without extended polymerization. This appears to aid VMD but does not assist with contrast development with the CA process and would not interact with dyeing agents in the same manner as the polymer chains.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…These analyses indicate zinc nanoparticle decoration of polycyanoacrylate fibrils, as well as zinc deposition associated with areas of fingermark ridges away from effective CA development. This process may relate to the improved definition of the print seen in other works (2,5,11) through zinc deposition on the nodular structure formed by superficial CA treatment, without extended polymerization. This appears to aid VMD but does not assist with contrast development with the CA process and would not interact with dyeing agents in the same manner as the polymer chains.…”
Section: Resultsmentioning
confidence: 75%
“…Initial examination shows that CA fuming produces polymerized CA mainly focused around pores in the latent fingermark. The application of gold and zinc through a VMD technique to a sample previously treated with CA causes the development of additional areas not coated with polycyanoacrylate, which relates to the improved definition of the print seen in other works (2,5,11). However, the primary interaction of the zinc deposition appears to be with the polycyanoacrylate, decorating the polymer chains with nanoscale particulates.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, the initial residue composition (point 1) is a combination of numerous substances from the epidermis [49], dermis [50], and extrinsic contaminants [51], with the exact properties dependent on the ratio of the three components [48]. Moreover, on point (3), it has been found that the porosity [52] and roughness [18] of the surface influence the composition and aging kinetics of a fingerprint, as they determine the adsorption rates of the water-soluble compounds in the residue and the effectiveness of the print detection scheme, respectively. As a result of the many confounding factors that contribute to the final characteristics of the print, it is necessary to utilize methods that both “look” and “feel” the print surface, as they not only provide information regarding the print’s owner, but also insight into the print’s composition and age.…”
Section: Resultsmentioning
confidence: 99%
“…AFM images have revealed sizeable variations in the morphology of various viruses and bacterial spores, and how these variations change with the nutrient exposure [16]. AFM images have been used to image fingerprint residue [17] and powder spray [8] and to set the baseline structures of polymeric [18] and metallic [19] surfaces employed in latent fingerprint development. Statistical analyses of AFM topography measurements of textile fibers exposed to environmental stress were used to illustrate the ability of nanoscale images to distinguish different environmental exposures [20].…”
Section: Introductionmentioning
confidence: 99%